Hybrid Push-Pull Endoscopic and Laparoscopic Full Thickness Resection for the Minimally Invasive Management of Gastrointestinal Stromal Tumors: A Pilot Clinical Study - Field F. Willingham; Paul Reynolds; Melinda Lewis; Andrew Ross; Shishir K. Maithel; Flavio G. Rocha (Gastroenterology Research and Practice)
Background. Gastric gastrointestinal stromal tumors (GISTs) that are predominantly endophytic or in anatomically complex locations pose a challenge for laparoscopic wedge resection; however, endoscopic resection can be associated with a positive deep margin given the fourth-layer origin of the tumors. Methods. Patients at two tertiary care academic medical centers with gastric GISTs in difficult anatomic locations or with a predominant endophytic component were considered for enrollment. Preoperative esophagogastroduodenoscopy (EGD), endoscopic ultrasound (EUS) with or without fine needle aspiration (FNA), and cross-sectional imaging were performed. Eligible patients were offered and consented for hybrid and standard management. Results. Over ten months, four patients in two institutions with anatomically complex or endophytic GISTs underwent successful, uncomplicated push-pull hybrid procedures. GIST was confirmed in all resection specimens. Conclusion. In a highly selected population, the hybrid push-pull approach was safe and effective in the removal of complex gastric GISTs. Endoscopic resection alone was associated with a positive deep margin, which the push-pull technique manages with a laparoscopic, full thickness, R0 resection. This novel, minimally invasive, hybrid laparoscopic and endoscopic push-pull technique is a safe and feasible alternative in the management of select GISTs that are not amenable to standard laparoscopic resection.